Axitinib in metastatic renal cell carcinoma. Issue 5 (May 2015) - Albiges, Laurence; Gizzi, Marco; Carton, Edith; Escudier, Bernard
<x xml:space="preserve">Abstract</x> Axitinib is the most recent targeted therapy approved by the US FDA and EMA in the treatment of metastatic renal cell carcinoma (mRCC). It is a second-generation, orally available, potent tyrosine kinase inhibitor targeting selectively VEGF receptor (VEGFR)-1, -2 and -3, resulting in inhibition of angiogenesis, metastasis and tumor growth. Based on the results of a randomized pivotal Phase III clinical trial, axitinib stands as one of the two recommended agents for patients with mRCC who progressed after first-line tyrosine kinase inhibitor therapy. Its potent and selective inhibition of VEGFR was the rationale for its development in the second-line setting after failure of prior cytokines or sunitinib. Here we examine the preclinical and clinical data of axitinib for mRCC, and its use in the treatment algorithm.